"Live in Israel. Live the Dream": Identity, Belonging, and Contemporary American Jewish Migration to Israel. Issue 3 (3rd July 2017) - Palmer, Zachary D.; Kraus, Rachel
ABSTRACT: Most current sociological literature on migration examines international moves to the United States and internal migration. Scant research addresses religious migration out of the United States. Utilizing in-depth, semi-structured interviews, we explore motivations behind recent American Jewish migration to Israel and how Jewish identity plays a role in the decision to move. We find that a combination of religious and cultural factors, Zionism, social networks, and the desire for a new start play a major role in motivating migration to Israel. Jewish identity is a common thread across these motivations. Many participants created a strong bond between their Judaism and Israel, viewing their connection to Israel as a way to belong to a larger community and demonstrate their attachment to Judaism. We discuss the implications for studying religious emigration from the United States that move beyond traditional economic models.